2006
DOI: 10.1089/thy.2006.16.177
|View full text |Cite
|
Sign up to set email alerts
|

Early Sequential Changes in Serum Thyroglobulin After Radioiodine Ablation for Thyroid Cancer: Possible Clinical Implications for Recombinant Human Thyrotropin-Aided Therapy

Abstract: TNM status and posttherapy whole-body scan findings aid in risk stratification of patients with thyroid cancer during initial therapy. Recently, the thyroglobulin (Tg) value measured during hypothyroidism just before 131I therapy (preablation Tg) has proved to be effective for predicting persistent/recurrent disease. In this study, we assessed the changes in serum Tg 48 hours after radioiodine ablative therapy performed in the hypothyroid state in order to evaluate if this parameter could be used in recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 8 publications
(8 reference statements)
0
23
0
Order By: Relevance
“…Second, stimulated Tg was measured 2 days after the first rhTSH injection, immediately before the radioiodine treatment, thus resulting in lower Tg values than those expected at 4 days (13,14). The main advantage of assessing rhTSH-stimulated Tg before radioiodine ablation is to overcome the serum Tg increase due to the effects of radiation on thyroid remnants (15). Third, the present data strongly suggest that the stimulated Tg level is related to the burden of PRD.…”
Section: Discussionmentioning
confidence: 71%
“…Second, stimulated Tg was measured 2 days after the first rhTSH injection, immediately before the radioiodine treatment, thus resulting in lower Tg values than those expected at 4 days (13,14). The main advantage of assessing rhTSH-stimulated Tg before radioiodine ablation is to overcome the serum Tg increase due to the effects of radiation on thyroid remnants (15). Third, the present data strongly suggest that the stimulated Tg level is related to the burden of PRD.…”
Section: Discussionmentioning
confidence: 71%
“…Many reports indicate the usefulness of Tg concentration measurement before radioiodine treatment to early detect DTC relapse or metastases. However, the stimulated Tg cannot be used instead of pre‐ablative offT4‐Tg when rhTSH is employed to prepare radioiodine ablation 3–5,8 . Excluding thyroid cells damage, two factors determine Tg concentration in most clinical situations: thyroid cell mass and activation of TSH receptors 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The Tg levels must be measured 48 h after radioiodine administration when rhTSH is used as stimulation 7 . Consequently, due to the radioiodine‐induced thyroid cells damage and Tg release, the Tg measurement would not have reliable predictive value in patients stimulated by rhTSH 8 . The present study was then undertaken to evaluate if Tg measurement before rhTSH administration and under T4 (onT4‐Tg) predicts post‐ablative scan results and patients’ outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This is after the ablative dose of RAI, which could impact Tg levels on the basis of radiationinduced tumor lysis. One study examined the effect of this intervening ablative dose of RAI on Tg levels and found that Tg levels increased after RAI therapy due to acute radiation effects (Taieb et al 2006). Because of the two simultaneous stimuli to Tg levels, rhTSH and RAI tumor destruction, this paradigm would not result in Tg levels that would be comparable to values obtained in diagnostic settings.…”
Section: Logistic Issues With Rhtsh Stimulated Thyroid Remnant Ablationmentioning
confidence: 99%